Religiusitas sebagai Upaya Pencegahan Kecurangan Akademik: Pendekatan Eksperimen - Simabur, Lisda Ariani; M, Effendi; Suhandoko, Astri Dwi Jayanti; Zainuddin, Zainuddin (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
This study aims to analyze the role of religiosity in mitigating academic fraud within face-to-face tutorial services at Universitas Terbuka UPBJJ Ternate, emphasizing that strengthening students' intellectual honesty can serve as a preventive measure. Academic fraud, particularly in academic environments, is often linked to lapses in ethical judgment and can be influenced by enhancing students' moral cognition and religiosity. To address this, the study implemented an intervention wherein pre-tutorial discussions on religious and moral values encouraged reflection on academic integrity, with the expectation that such reflections would improve ethical decision-making and reduce tendencies toward academic fraud. The experimental design involved a pretest-posttest control group structure with 78 participating students, where the treatment group engaged in religiosity and morality discussions focused on academic honesty principles. Data were analyzed using paired sample t-tests, showing a significant improvement in students’ learning outcomes and a reduction in academic fraud tendencies post-intervention. This study uniquely positions itself as the first in Indonesia to examine academic fraud through the pentagon fraud framework using an experimental model, highlighting the effectiveness of religiosity-based ethical discussions in fostering academic integrity.